2017
DOI: 10.11646/zootaxa.4356.1.1
|View full text |Cite
|
Sign up to set email alerts
|

European species of the aphid genus Eulachnus Del Guercio, 1909 (Hemiptera: Aphididae: Lachninae): revision and molecular phylogeny

Abstract: The aphid genus Eulachnus in Europe is revised to include 12 species, using an integrative taxonomy approach, based on morphometric, molecular and biological traits. Fundatrix, apterous and alate viviparous female of a new species–Eulachnus stekolshchikovi Kanturski sp. nov. are described. Neotypes are designated for E. agilis, E. brevipilosus and E. nigricola. Lectotypes are designated for E. alticola, E. cembrae, E. rileyi and E. tuberculostemmatus. New synonyms are proposed: E. abameleki syn. nov. (= Cinara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Such incongruence also occurs at lower taxonomic levels. Most of the attempts to identify phylogenetic relationships based on molecular data are for Aphidinae [53–55,58,8283], Eriosomatinae [59,8487], Hormaphidinae [8891] and Lachninae [57,9295]. Analyses based on a total-evidence dataset are rather rare [37,91].…”
Section: Discussionmentioning
confidence: 99%
“…Such incongruence also occurs at lower taxonomic levels. Most of the attempts to identify phylogenetic relationships based on molecular data are for Aphidinae [53–55,58,8283], Eriosomatinae [59,8487], Hormaphidinae [8891] and Lachninae [57,9295]. Analyses based on a total-evidence dataset are rather rare [37,91].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only nymphs and viviparous females were found during the sampling period; no sexual morphs were found. Although E. tuberculostemmatus has been known as a holocyclic species and its sexual morphs have been described (Kanturski et al, 2017), it seems to be anholocyclic in our region. Wieczorek et al (2013) reported sexuales of Pterochloroides persicae (Cholodkorsky) from Isfahan, Iran, and concluded that the Isfahan climate (with hot summer and cold winter) is favourable for the production of sexual morphs of aphids.…”
Section: Discussionmentioning
confidence: 76%
“…The palaearctic genus Eulachnus possesses 12-18 morphologically described species (Kanturski et al, 2015(Kanturski et al, , 2017, which usually feed in small groups of several individuals, including one to three adult females and a few larvae (Kanturski & Wieczorek, 2014;Blackman & Eastop, 2019). They are always associated with Pinus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of accessory sensilla arrangement is different than in the other lachnids that have been analysed to date. In the Eulachnini genus Eulachnus , the accessory sensilla are located under the major rhinarium (large placoid sensillum) 46 , while in Pseudessigella one (small placoid sensillum) is separated from the others and is located on the side of the major rhinarium 47 . Although only the arrangement of sensilla of Tuberolachnus salignus is so far known in the tribe Tuberolachnini, it is very different from that of Nippolachnus in which all of the accessory rhinaria are arranged linearly on the side of the major rhinarium, in all of the cases that are known, the accessory rhinaria lie on the basal part of the last antennal segment 48 .…”
Section: Discussionmentioning
confidence: 99%